Being a Woman under Taliban’s Theocratic Regime - Kallini, Stavroula Xristina (HAPSc Policy Briefs Series, 2021)
In the light of the recent events that have taken place in Afghanistan, the purpose of this policy brief is to turn back to the time when the Taliban were in power (1996-2001) and to explore the brutality of their theocratic regime against women. In particular, this policy brief examines the restrictions imposed by the Taliban on Afghan women, by depriving them of essential rights, as well as the changes that are claimed to have taken place in the post-Taliban era. It is concluded that the international community and NGOs should play a significant role in upgrading the position of women in Afghan society.